Hubungan Pemerintah Pusat dan Daerah: Kajian terhadap Efektivitas Pengelolaan Dana Otonomi Khusus di Provinsi Aceh - Ridwan, Mahlil; Affandi, Hernadi; Junaenah, Inna (Faculty of Law, University of Dr. Soetomo, 2023)
Basically, the Aceh Special Autonomy Fund policy is to provide wider authority for local governments and the people of Aceh to regulate and take care of themselves within the framework of the Republic of Indonesia. This broader authority also includes the authority to regulate the use of natural resources in the Aceh Province area, as much as possible for the prosperity of the Acehnese people, empowering their economic, social, and cultural potential, including providing a significant role for the indigenous people of Aceh to be involved in the process of formulating regional policies, determining development strategies while still respecting the equality and diversity of people's lives in the Province Aceh. Therefore, the author reviews the relationship between central and regional authorities in the Republic of Indonesia with the regions, especially Aceh in the Special Autonomy Law with qualitative methods and through understanding the concept of decentralization. The results clearly show that, however, the implementation of the Special Autonomy Fund in Aceh is different from what is described in autonomy as stated in the law. In fact, in the field, so far, the central government's assistance, coaching and supervision have not been seen.